Efektivitas Project Based Learning dalam Kurikulum Merdeka Pada Pembelajaran Aktivitas Pengembangan Terhadap Minat Belajar Siswa Sekolah Menengah Kejuruan - Kuntoro Aji; Ega Trisna Rahayu (Jurnal Ilmiah Wahana Pendidikan, 2023)
The existence of this research is motivated by a copy of the circular letter of the decision of Mentri Pendidikan, Kebudayaan, Riset, dan Teknologi Nomor 56/M/2022 pada tanggal 11 Febuari 2022 on Guidelines for Curriculum Implementation in the Context of Learning Recovery. This study aims to determine the effectiveness of Project Based Learning in the Merdeka Curriculum in Learning Development Activities on Student Learning Interest at SMKN 1 Jayakerta. On Development Activity Learning towards Student Learning Interest at SMKN 1 Jayakerta. The type of approach in this research is a quantitative descriptive approach using survey research methods. The population in this study were students of class X SMKN 1 Jayakerta. The research sample consisted of 27 students using cluster random sampling technique. Data collection techniques using questionnaires or anget. Data processing techniques using the Microsoft Excel program. The results of this study indicate that there is an increase in student interest in learning after being given the project-based learning model treatment with consideration of the highest frequency in the pretest in the low category as many as 10 students or 37.04%. Consideration of the highest frequency in the posttest was in the moderate category as many as 13 students or 48.15% had an interest in learning development activities.